Bochdalek hernia associated with intestinal malrotation as an incidental finding in an adult patient: case report - Alvarez-Rojas, Andres F.; Alvarez-Sores, Erik; Ortiz-Higareda, Vanessa; Martínez-Ordaz, José L. (International Journal of Research in Medical Sciences, 2023)
Bochdalek hernia (BH) is the most common congenital diaphragmatic hernia, however in adults the clinical presentation and diagnosis is rare. Intestinal malrotation (IM) is a congenital anomaly that results in an alteration in intestinal anatomy secondary to inadequate intestinal rotation, which occurs at the end of the first trimester of embryonic development, some digestive anomalies may be related, such as diaphragmatic hernia, its Diagnosis is made in the neonatal period although it can be diagnosed in older children and adults, debuting with symptoms of intestinal obstruction or being an incidental finding. Below we present a case report of an adult patient with a diagnosis of Bochdalek congenital diaphragmatic hernia (CDH) in whom an incidental diagnosis of IM was made, who underwent elective surgery, performing laparoscopic diaphragmatic plasty with favorable results.